MENINGKATKAN KEMAMPUAN MENULIS TEKS DESKRIPSI MENGGUNAKAN MEDIA KARTU BERGAMBAR PADA SISWA KELAS VII SMPN 27 MEDAN - Situmorang, Rudolf Pranholiver; Isman, Mhd; Panjaitan, Hermina (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This study aims to determine the improvement of writing skills in descriptive texts using picture cards among seventh-grade students at SMPN 27 Medan. This research uses the classroom action research method conducted over 2 cycles. In this research, there are stages of planning, implementation, observation, and reflection. The instruments used are an activity observation sheet and a writing test for descriptive texts using picture cards as media. The research results show that the use of picture cards is effective in improving the descriptive writing skills of seventh-grade junior high school students. The improvement is evident in various aspects, such as the clarity of descriptions, text structure, vocabulary usage, as well as the cohesion and coherence of the text. Students also become more motivated to write because the learning feels more engaging and interactive.